Principles of Mathematics in Operations Research - Kandiller, Levent; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2007)
Principles of Mathematics in Operations Research is a comprehensive survey of the mathematical concepts and principles of industrial mathematics. Its purpose is to provide students and professionals with an understanding of the fundamental mathematical principles used in Industrial Mathematics/OR in modeling problems and application solutions. All the concepts presented in each chapter have undergone the learning scrutiny of the author and his students. The conceptual relationships within the chapter material have been developed in the classroom experience working with the students' level of understanding. The illustrative material throughout the book (i.e., worked-out problems and examples of the mathematical principles) was refined for student comprehension as the manuscript developed through its iterations, and the chapter exercises are refined from the previous year's exercises. In sum, the author has carefully developed a pedagogically strong survey textbook of OR and Industrial Mathematics.
Preliminary Linear Algebra -- Orthogonality -- Eigen Values and Vectors -- Positive Definiteness -- Computational Aspects -- Convex Sets -- Linear Programming -- Number Systems -- Basic Topology -- Continuity -- Differentiation -- Power Series and Special Functions -- Special Transformations.
Keywords: Mathematical models; Operations research; Decision making; Applied mathematics; Engineering mathematics; Computer mathematics; Mathematical optimization; Business; Management science; Mathematical Modeling and Industrial Mathematics; Operations Research/Decision Theory; Applications of Mathematics; Computational Mathematics and Numerical Analysis; Optimization; Business and Management, general